IMPLEMENTATION OF LEARNING CYCLE 7E MODEL TO PRACTICE METACOGNITIVE SKILLS ON REACTION RATE MATTER - Rosa, Dinda Diana; Azizah, Utiya (Universitas Negeri Surabaya, 2017)
The purpose of this research is to describe the implementation of Learning Cycle 7E modelsto practice students' metacognitive skills on reaction rate material at XI grade in SMAN 1 Taman. Theresearch instrument used is the implementation observationsheet of Learning Cycle 7E models,student activity sheet, test of metacognitive skill, and inventory metacognitive. The design of this studyis